Resonating voices: unpacking EFL teachers’ beliefs regarding pronunciation instruction in Chinese tertiary context - Wang, Juan; Ahmad, Norhakimah Khaiessa; Jamil, Halimah; Darmi, Ramiaida; Ahmad, Farah Amira; Norhisham, Siti Nurhidayah; Mohamad Sukri, Muhammad Zulfazli; Rosli, Nur Rafiqah; Saif, Siti Norazrina; Basarudin, Nurul Izzati; Azzam-Sayuti, Mohamad; Abdul Karim, Akmal Hayat (Sciedu Press, 2025)
This study investigates the beliefs of three English as a Foreign Language (EFL) teachers regarding pronunciation instruction at a university in Northwest China, focusing on an area that remains under-explored in Chinese contexts. Data was collected using semi-structured interviews and narratives. The findings demonstrated that, despite recognizing the significance of pronunciation in language learning, the teachers’ approach to pronunciation instruction was often unsystematic and reactive, primarily addressing segmental errors through corrective feedback. In addition, the teachers’ trajectories of pronunciation beliefs were shaped by several factors, including their own educational backgrounds, the constraints of the curriculum, the perceived needs of their students. Furthermore, insufficient professional development opportunities led to the undervaluation of pronunciation in their teaching practices. These findings underscore the necessity for tailored teacher education programs that provide a range of effective strategies for pronunciation teaching. By offering systematic and comprehensive training, such programs could help close the gap between teachers’ beliefs and practices, thereby enhancing the overall quality of pronunciation instruction in EFL classrooms.